The changing geography of urban tourism: Will the center hold? - Spirou, Costas; Judd, Dennis R. (Routledge, 2014)
Using the case of metropolitan Chicago, the paper focuses on the evolving geography of urban tourism by examining how far satellite cities have embraced a strategy of development that mirrors the city of Chicago's strategy. The paper argues that, at least in the case of some metropolitan areas in the U.S. tourism development at the urban periphery may compete with and therefore slow the pace of redevelopment at the urban core.
Keywords: Stadtplanung; Fremdenverkehr; Zielgebiet; Freizeit; Innenstadt; Altstadt; Stadtkern; Stadtgeschichte; Stadtumland; Tourismus; Städtetourismus; Tagestourismus; Satellitenstadt; Identität